Knowledge of postpartum care and postbirth warning signs among midwives in Ghana. Issue 4 (26th November 2019) - Adams, Yenupini Joyce; Ray, Herman E.
Abstract: Background: In Ghana, midwives are the primary maternity care practitioners. Their knowledge of postpartum care is critical for preventing and reducing maternal deaths because it affects the quality of care provided to women. In addition, midwives' knowledge of postbirth warning signs is important for early identification and management of complications. This study assessed midwives' knowledge of postpartum care and postbirth warning signs to develop interventions to improve patient care. Methods: A cross‐sectional survey of 246 midwives was conducted in the four main hospitals of Tamale, Ghana. Data were collected using a postpartum care knowledge questionnaire developed by JHPIEGO. Data were analyzed in SAS version 9.4 using descriptive, bivariate, and multivariate statistics. Results: Mean age of midwives was 31.9 years. The percentage of midwives who responded correctly to each postpartum care question ranged from 41.6% to 84.9%. Most midwives were knowledgeable about breastfeeding—however, knowledge about fundus location, postpartum examination, and care during first 2 hours postpartum was low. Hospital was associated with knowledge of postpartum care ( P < .001). Only 28.1% of midwives identified all nine warning signs of complications. Most midwives could identify severe bleeding, severe headaches, and high temperature as warning signs—however, knowledge of warning signs of some life‐threatening complications such as chest pain, obstructed breathing, and thoughts of hurting oneself was low. More years of experience was associated with better knowledge of postbirth warning signs ( P = .03). Discussion: Findings suggest a need for additional training of midwives in how to care for postpartum patients and accurately identify warning signs for life‐threatening complications.